Molecular characterization of herbicide resistance in Palmer amaranth (Amaranthus palmeri S.Wats) populations in South Africa - Vorster, Barend Juan (University of Pretoria, 2022)
Dissertation (MSc (Plant Sciences))--University of Pretoria, 2021.